A multimodal atlas of the molecular and cellular changes to cortex driven by Alzheimer's disease. (20th December 2022) - Travaglini, Kyle J; Gabitto, Mariano; Ding, Yi; Ariza, Jeanelle; Chakrabarty, Rushil; Crane, Paul K.; Ferrer, Rebecca; Goldy, Jeff; Grabowski, Thomas J; Guilford, Nathan; Guzman, Junitta; Hawrylycz, Michael J; et al.
Abstract: Background: Alzheimer's disease (AD) is the most common form of dementia, which can be detected early as mild cognitive impairment but has no broadly effective treatments to halt patients' yearslong decline. Histopathology studies have long noted dramatic, progressive, and stereotyped changes across numerous brain regions, including protein aggregate formation and even selective loss of molecularly defined neuronal populations. But the underlying molecular and cellular mechanisms that cause AD and facilitate its progression remain unknown or are only coarsely understood, hampering efforts to treat or cure the disease. Method: To uncover these mechanisms, we characterized the transcriptomic and epigenetic landscapes of AD by applying single nucleus RNA and ATAC sequencing to ∼8 million nuclei isolated from 3 cortical regions (entorhinal cortex, middle temporal gyrus, and prefrontal cortex) in 84 aged donors that span the histopathological and cognitive disease spectrums (including unaffected controls) as part of a broader Seattle AD Brain Cell Atlas (SEA‐AD) effort. We identified ∼130 highly resolved transcriptional cell types from the BRAIN initiatives' neurotypical references and leveraged recently developed machine learning approaches to integrate and hierarchically classify nuclei across donors. This enabled characterization of cell type abundance, gene expression, and chromatin accessibility differences that correlate with AD neuropathology, cognition decline, and genetic background with unprecedented precision. Result: Our comprehensive molecular atlas identified specific intratelencephalic excitatory neurons, inhibitory neurons, and microglia subsets that have altered abundances, gene expression, and/or chromatin accessibility as a function of cognitive decline and quantitative neuropathology, suggesting these populations may be selectively vulnerable to AD or involved in disease etiology. Their differentially expressed genes and accessible chromatin regions include both those found by previous atlasing efforts and genome wide association studies as well as novel ones, providing new clues to the molecular pathways that underpin AD. By comparing the SEA‐AD atlas with the neurotypical references, we also identified how expression patterns of genes, chromatin accessibility, and cell‐cell interactions associated with AD are more broadly altered by the disease. Conclusion: The cell types and molecular pathways identified by our atlas provide new targets for the rational development of therapeutic interventions and as biomarkers for earlier detection of the disease.